Morphology of alveolate species of the genus Cocconeis (Cocconeidaceae, Bacillariophyta) with the description of Monoalveoneis gen. nov. - Yurchak, Maria; Gogorev, Rinat; Sokolova, Irina; Kezlya, Elena; Doan-Nhu, Hai; Kulikovskiy, Maxim (Phytotaxa, 2025)
A new genus Monoalveoneis gen. nov. is proposed based on the results of morphological analysis of some Cocconeis taxa. The new genus is characterised by a distinct type of alveoli, which has large elongated openings on the outside of the valve and small foramina on the inside. A new term, monoalveolus, is suggested to describe this type of structure. Besides a special type of areolae, the new genus is characterized by high edge of both valvocopulae and shape of their fimbriae. The variety of alveoli structure in various groups of diatoms is discussed.